An investigation into molecular biomarkers of pulp inflammation and cell death and their potential use as a diagnostic tool. - Lennon, Síle Orlaith (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2024)
The overarching aim of the thesis was to present a robust method of collecting and analysing pulpal blood, to inform quality biomarker discovery with the potential to detect the `threshold? between teeth amenable to vital pulp treatment (VPT) and those that require root canal treatment. A suite of studies was presented in order to address these aims. Universal methodology was presented in Chapter 2, informed by certain weaknesses identified in the existing literature. In order to achieve a predictable and reproducible diagnostic testing methodology, several other aims were proposed: To ascertain the most appropriate vehicle in which to collect the pulpal blood sample, investigate the most effective blood analyte (serum, or plasma), as well as establishing the most appropriate laboratory testing technique (total protein, or volumetric) to predictably analyze the pulpal condition. An effective, simple and reproducible method of collecting pulpal blood was established. The data highlighted some practical, technical and logistic difficulties with pulpal blood collection and identified pulp sampling methods that work, the value of plasma over serum and a collection protocol that could be introduced into routine practice and research activities. The visual appearance of the exposed pulp was correlated with both traditional and novel pulp diagnostic classification systems, based on symptoms and caries depth. These factors were then linked with VPT outcomes, after at least one year. The catalogue of images captured at various stages in the management of exposed pulps demonstrated marked variation in character, volume and ease with which bleeding could be stemmed. As a result, other factors may play a significant role in the decision-making process. Although the ability to arrest pulpal bleeding appears to be a good predictor of pulpal health, it is prone to subjectivity in relation to its acquisition and other operator characteristics, therefore an objective quantifiable biomarker level would be a desirable adjunct. The identification of the start-point of irreversible damage, namely necrosis, may present a novel target biomarker to differentiate pulpal states. An assay targeting circulating extracellular histones was employed to represent pulp cell death complemented by a quantitative ELISA measuring HMGB? capable of differentiating regulated from accidental cell death, with a view to developing a discriminatory chairside diagnostic test. A number of cases produced high expressions of selected cell death mediators. These cases related to the presence of micro-abscess in more than half of the samples and a uniform inability to obtain sufficient haemostasis to provide pulp preservation procedures, which could not have been determined prior to accessing the pulp. Cases requiring pulpectomy and expressing low levels of circulating extracellular histones, were exclusive to the most severe category of pulpitis. The value of investigating multiple biomarkers associated with the interrelated process of inflammation, coagulation and sepsis may assist in the clinical decision making, as well as prognostic information in terms of disease management Circulating histones and selective DAMPs present novel diagnostic targets, however, more studies are necessary with larger patient numbers and multiple, calibrated clinical operators. Utilisation of a profiling approach via an antibody array or other high-throughput technologies allows simultaneous analysis of multiple mediators and processes, while maximising the information gathered from minute volumes of substrate available- a drawback unique to the collection of pulpal blood. Multiplex analysis of inflammatory serum cytokines, obtained from carefully characterised blood samples representing health through progressive inflammation, provides a reliable, cost effective screening tool to inform useful targets for further investigations using candidate ELISA analyses. Initial validation assays revealed promising results with several markers identifying significant differences in expression between the diagnostic categories. A significant drawback in the analysis of pulpal blood is the limited availability of substrate to provide multiple analyses. Preliminary operating procedures should take account of the collected volumes of substrate necessary to provide standardised dilution. Within the limitations of the model presented, an opportunity exits to direct larger studies combining a profiling approach with candidate validation, to direct future standards of biomarker identification in pulpal blood that can direct clinical treatment.
APPROVED
Keywords: pulp diagnostics; biomarker discovery; cell death; pulpal bleeding; inflammation